Continuous dialysis of hydrochloric acid and sodium chloride mixture - Palatý, Zdeněk; Bendová, Helena (Marcel Dekker Inc, 2017)
Using a two-compartment counter-current dialyzer with single passes, the simultaneous transport of hydrochloric acid and sodium chloride through an anion-exchange membrane Neosepta-AFN was studied at steady state. The diffusion dialysis process was quantified by four membrane mass transfer coefficients, which were correlated with the hydrochloric acid and sodium chloride concentrations in the feed. These characteristics were calculated from the experimental data on dialysis using a two-step procedure combining the numerical integration of the basic differential equations and a multivariable optimization. The second step of this procedure ensured the best agreement between the experimental and calculated data.
Kontinuální dialýza směsi kyseliny chlorovodíkové a chloridu sodného
Keywords: Anion-exchange membrane; continuous dialyzer; diffusion dialysis; hydrochloric acid; sodium chloride; aniontově-výměnná membrána; kontinuální dialyzér; difuzní dialýza; kyselina chlorovodíková; chlorid sodný